The research of the diesel engine performance and emission characteristics when operating on three-component fuel - Labeckas, Gvidonas; Slavinskas, Stasys (2011)
The article deals with bench testing results of a four stroke, four cylinder, unmodified, naturally aspirated, DI diesel engine operating on reference (DF) arctic class 2 diesel fuel (80vol%), anhydrous (200 proof) ethanol (15vol%) and rapeseed methyl ester (5vol%) blend B15E5. The purpose of the research is to investigate the effect of simultaneous ethanol and RME addition in the diesel fuel on brake specific fuel consumption (bsfc) of the engine, the brake thermal efficiency (nj and noxious emissions, including NO, NO2, NOX, CO, CO2, HC and smoke opacity of the exhausts. The bsfc of the diesel engine operating on three-component fuel B15E5 under maximum load of bmep — 0.75, 0.76 and 0.68 MPa is higher by 10.3%, 10.7% and 9.6% because of both net heating value lower by 6.18% and brake thermal efficiency lower by 3.4%, 3.7% and 2.8% relative to that of a neat diesel at corresponding 1400, 1800 and 2200 min speeds. The maximum NOX emission produced from oxygenated blend B15E5 was reduced by 13.4%, 18.0% and 12.5% and smoke opacity diminished by 13.2%, 1.5% and 2.7% under considered loading conditions relative to that of reference diesel fuel. As a penalty for advantages obtained in having a better NOX emission, the CO amounts produced from three-component fuel Bl 5E5 were lowered by 6.0% for low 1400 min speed only and they increased by 20.1% and 28.2% for higher 1800 and 2200 min'1 speeds and the HC emissions were also higher by 35.1%, 25.5% and 34.9% throughout a whole speed rage comparing with respective values measured from neat diesel fuel. Residual oxygen O2 content in the exhausts was lower by 5.0%, 7.4% and 4.3% and carbon dioxide CO2 emissions were higher by 2.8%, 3.4% and 2.4% when operating under fully opened throttle on three-component fuel B15E5 comparing with respective values suggested by reference diesel fuel at 1400, 1800 and 2200 min speeds.